2021
DOI: 10.1136/jitc-2021-002508
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticles inflame tumors to overcome anti-PD-1 resistance through TLR4-NFκB axis

Abstract: BackgroundThe clinical benefits of antiprogrammed cell death protein 1 (PD-1) therapy are compromised by resistance in immunologically cold tumors. Convergence of immunotherapy and bioengineering is potential to overcome the resistance. Mesoporous silica nanoparticles (MSNs) are considered the most promising inorganic biological nanomaterials for clinical transformation, however, the fundamental influence of MSNs on immunotherapy is unclear. In this study, we aimed to investigate the role of MSNs in tumor rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Recent studies have shown that silica nanoparticles promote the tumor infiltration of CD8+ cytotoxic T lymphocytes (CTLs) by targeting the TLR4 /NF-κB pathway. Through PD-1 blockade, the depletion of CTLs is activated and reversed, thereby generating durable antitumor immunity ( Sun et al, 2021 ). Recent findings in chronic inflammatory diseases and cancer indicate that T-cell failure and lymphopenia may be related to changes in the expression level of TLR4 ( Wild et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that silica nanoparticles promote the tumor infiltration of CD8+ cytotoxic T lymphocytes (CTLs) by targeting the TLR4 /NF-κB pathway. Through PD-1 blockade, the depletion of CTLs is activated and reversed, thereby generating durable antitumor immunity ( Sun et al, 2021 ). Recent findings in chronic inflammatory diseases and cancer indicate that T-cell failure and lymphopenia may be related to changes in the expression level of TLR4 ( Wild et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that biomaterials at the nanoscale have been explored to establish a T-cell-inflamed TME and overcome resistance to ICB. Mesoporous silica nanoparticles were reported to elicit T-cell-recruitment chemokine production and drive CTL infiltration in multiple tumor models resistant to PD-1 antibodies ( 149 ). A supramolecular gold nanorod has been reported to reprogram the TME and improve TILs, significantly augmenting ICB therapy, which depends on the hyperthermal activation of ICD and genome editing of PD-L1 ( 209 ).…”
Section: Strategies In Overcoming Resistance To Immune Checkpoint Blo...mentioning
confidence: 99%
“…Chemokines Ccl5/Cxcl9/Cxcl10 released by macrophages encouraged MSN-induced CTL infiltration and blockade of the TLR4-NFκB axis in macrophages or CTL revoked MSNinduced resensitization to anti-PD-1 therapy. 182 Chandra and colleagues prepared manganese (Mn 4+ )-doped silica nanoparticles (Mn 4+ -SNP) with a large pore size to incorporate the viral neoantigen peptide GF001 obtained from HPV16 E7 oncoprotein. They revealed that Mn 4+ -SNP acted as selfadjuvants via ROS generation, dendritic cell stimulation, and maturation.…”
Section: Application Of Silica Nanoparticles In Cancer Targetingmentioning
confidence: 99%
“…MSN aided in the prompt development of a T cell-inflamed microenvironment with the stimulation of interferon-γ/tumor necrosis factor-α/perforin/granzyme B with little effect on PD-1/lymphocyte-activation gene 3 (LAG-3)/T-cell immunoglobulin and mucin-domain containing-3 (TIM-3) CTL. Chemokines Ccl5/Cxcl9/Cxcl10 released by macrophages encouraged MSN-induced CTL infiltration and blockade of the TLR4-NFκB axis in macrophages or CTL revoked MSN-induced resensitization to anti-PD-1 therapy . Chandra and colleagues prepared manganese (Mn 4+ )-doped silica nanoparticles (Mn 4+ -SNP) with a large pore size to incorporate the viral neoantigen peptide GF001 obtained from HPV16 E7 oncoprotein.…”
Section: Application Of Silica Nanoparticles In Cancer Targetingmentioning
confidence: 99%